Effect of a liquid multivitamin/mineral supplement on anaerobic exercise performance - Fry, A. C.; Bloomer, R. J.; Falvo, M. J.; Moore, C. A.; Schilling, B. K.; Weiss, L. W. (Research in Sports Medicine, 2006)
The purpose of this study was to determine if supplementation with a liquid multi-vitamin/mineral would improve anaerobic exercise performance. Fourteen resistance-trained men performed a 30-second cycle sprint and one set of squat exercise on 2 separate days before and following 8 weeks of supplementation with either a liquid multi-vitamin/mineral or a placebo. Heart rate, perceived exertion, blood lactate, peak and mean power, and rate of fatigue were determined for all tests. No differences were noted for any variable (P > 0.05). When controlling for presupplementation values, however, a decreased rate of fatigue was noted for both exercise tests following the multi-vitamin/mineral supplementation. These data suggest that in resistance trained men consuming a nutritionally sound diet, supplementation with a liquid multi-vitamin/mineral does not favorably impact most anaerobic exercise performances. Such supplementation, however, may result in a minor decreased rate of fatigue. It appears that, in terms of improved short duration anaerobic exercise performance, supplemental micronutrients may not be efficient ergogenic agents for well-trained individuals consuming an adequate diet.